ANALISIS PENGARUH KOMPENSASI TERHADAP KEPUASAN KERJA PEGAWAI NEGERI SIPIL DINAS PENDIDIKAN KOTA BLITAR - Esti Widasih; Arisyahidin Arisyahidin; Sumarji Sumarji (Universitas Islam Kadiri, 2019)
This study aims to determine the effect of intrinsic compensation and extrinsic compensation to job satisfaction of Civil Servants of Blitar City Education Office either partially or jointly. In doing research the method used is descriptive quantitative with data analysis using multiple linear regression. The respondents as a sample of 80 of 100 employees in the Education Office of Blitar City. The result of hypothesis test shows that partial compensation effect of intrinsic compensation has significant positive effect and extrinsic compensation has positive and significant effect on job satisfaction. But these two independent variables simultaneously have a positive and significant effect on job satisfaction of Civil Servant of Education Office of Blitar City. The dominance of the effect of intrinsic compensation and extrinsic compensation on job satisfaction is smaller than the influence of other factors not examined.